Combating illicit fentanyl: Will increased Chinese regulation generate a public health crisis in India? - Wang, Chao; Lassi, Nicholas (Frontiers in Public Health, 2022)
This study examines how Chinese drug regulations are shifting illicit fentanyl production from China to India. This change has implications for the law, drug enforcement, public health, as domestic production increases domestic access to fentanyl, and the pharmaceutical industry in India. An empirical examination of current trends in fentanyl production and use in the region is conducted, along with an exegesis of the legal and regulatory systems in China and India. There is an accounting of the chemical and pharmaceutical industries, the strengths and weaknesses of drug legislation, and the public health consequences of increased production, distribution, and use of fentanyl in India. This study also details how the Indian government meets this challenge through legislative, enforcement, and public health mechanisms, foremost through class-wide legislative control over fentanyl and its precursors. Class-wide control prohibits the unlawful production and distribution of all current and future fentanyl analogues and their precursors, disincentivizing and disrupting their development and production. The Indian government should also reduce domestic demand by promoting harm reduction measures such as opioid substitution therapy, evidence-based treatment, fentanyl test strip and naloxone distribution, and needle exchange programs.